Stepfamilies and management of financial resources - Dotto, Valentina (Italian Sociological Review, 2012)
Stepfamily have been around for a long time and they are unlikely to go away. They are one of the fastest growing family types in industrial nation. Stepfamilies are complex and diverse: adding a stepparent post-divorce created new level of kin and new interaction pattern.The aim of the present study is to explore patterns of control and management of money by means of data from semi-structured interviews with 8 stepfamilies couple and to understand the economic behaviour of stepfamilies, the beliefs and values about household finances, and the relationship of financial management behaviour to family quality